1992
DOI: 10.1080/00206819209465662
|View full text |Cite
|
Sign up to set email alerts
|

HYDROTHERMAL MANIFESTATIONS AT PIYP subMARINE VOLCANO, BERING SEA

Abstract: A. M. Sagalevich , P. V. Torokhov , V. V. Matveyenkov , S. V. Galkin & L. I. Moskalev To cite this article: A. M. Sagalevich , P. V. Torokhov , V. V. Matveyenkov , S. V. Galkin & L. I.From: "Gidrotermal'nyye proyavleniya podvodnogo vulkana Piypa (Beringovo more)," Izvestiya Akademii Nauk, seriya geologicheskaya, 1992, No. 9,pp.l04-114. The shallow depth of the hydrothermal vents on Piyp Volcano, which rises to a depth of 352 m, is responsible for some unusual features, both mineralogical and biological. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…(1995), Jollivet et al. (1990), Ohta (1990a), Van Dover & Hessler (1990), Kim & Ohta (1991), Galkin (1992), Sagalevich et al. (1992), Carney (1994), Hashimoto et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1995), Jollivet et al. (1990), Ohta (1990a), Van Dover & Hessler (1990), Kim & Ohta (1991), Galkin (1992), Sagalevich et al. (1992), Carney (1994), Hashimoto et al.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Paralithodes is a fairly widespread and commonly encountered deep‐sea genus of lithodids. According to Chevaldonné & Olu (1996), Sagalevich et al. (1992) reported Paralithodes sp.…”
Section: Resultsmentioning
confidence: 99%
“…The southern top and slopes are composed of dacite pumice, while in its centre, a large hydrothermal structure, shaped like a long hill to 10 m height, is presented by mostly barite and Ca carbonate. On the southern top, the local vents are associated with small (up to 40 cm) conical carbonate structures [27].…”
Section: Study Areamentioning
confidence: 99%
“…The first data on the benthic communities at areas of hydrothermal manifestations of the Piip Volcano was obtained during the 22nd cruise of RV "Akademik Mstislav Keldysh" in 1990 using the human-occupied vehicle (HOV) "Mir" [27]. It was observed that on the northern and southern summits of the volcano, in addition to several active anhydrite and carbonate hydrothermal structures with focused methane emanations, there were large areas of diffuse emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation